The epidemiological impact and significance of carbapenem resistance in Pseudomonas aeruginosa bloodstream infections: a matched case–case-control analysis. (14th August 2018) - Aviv, Tzach; Lazarovitch, Tsillia; Katz, David; Zaidenstein, Ronit; Dadon, Mor; Daniel, Chen; Tal-Jasper, Ruthy; Kaye, Keith S.; Marchaim, Dror
Abstract: A case–case-control investigation (N = 255 patients) explored the epidemiology of carbapenem-resistant Pseudomonas aeruginosa (CRPA). Recent exposure to carbapenems and a rapidly fatal condition should prompt practitioners to shorten delays in initiating appropriate therapy, which can adversely impact CRPA outcomes, as opposed to the isolated impact of the carbapenem resistance determinant.